Exploring the potential of propanamide-sulfonamide based drug conjugates as dual inhibitors of urease and cyclooxygenase-2: biological and their in silico studies - Ahmad, Saghir; Abdul Qadir, Muhammad; Ahmed, Mahmood; Imran, Muhammad; Yousaf, Numan; Wani, Tanveer A.; Zargar, Seema; Ali, Ijaz; Muddassar, Muhammad (Frontiers in Chemistry, 2023)
Derivative synthesis has been a crucial method for altering the effects of already-approved medications, especially to lessen adverse effects and enhance results. Making use of this multi-target approach, a series of naproxen-sulfa drug conjugates was designed and synthesized. The newly designed conjugates were confirmed by spectroscopic techniques like IR, 1HNMR, 13CNMR, and elemental analysis. The conjugates were screened for anti-inflammatory, urease, and cyclooxygenase-2 (COX-2) inhibition. Naproxen conjugated with sulfanilamide, sulfathiazole, and sulfaguanidine was found potent and showed a competitive mode of urease inhibition, with IC50 (µM) values 6.69 ± 0.11, 5.82 ± 0.28, 5.06 ± 0.29, respectively. When compared to other screened conjugates, the naproxen-sulfamethoxazole conjugation showed better anti-inflammatory action by inhibiting induced edema by 82.8%, which is comparable to the medication indomethacin (86.8% inhibition). Whereas it exhibited 75.4% inhibition of COX-2 at 10 µM concentration which is comparable with the reference drug (celecoxib, 77.1% inhibition). Moreover, the binding modes of competitive inhibitors with the urease and COX-2 receptor were predicted through molecular docking studies and their stability analysis through MD simulations showed that these compounds made stable complexes with the respective targets and there were no conformational changes that occurred during simulation. The obtained results showed that the conjugates of approved therapeutic molecules may lead to the development of novel types of pharmacological agents in the treatment of several pathological disorders where urease and COX-2 enzymes are involved.